Open Borders in the Alps-Adriatic Region during the Cold War and Beyond: An ERC Project, an Exhibition, and a Twin European Capital of Culture - Tenca Montini Federico; Rutar Sabine (Comparative Southeast European Studies)
In this article, the authors present the ERC project Open Borders, conducted between 2023 and 2027 at the Science and Research Centre (ZRS) in Koper, Slovenia. The project redefines Cold War history through multidisciplinary research on people, places, and cross-border practices. It examines transnational interactions in the social, cultural, and political context of the Cold War, and beyond, in the border region between Austria, Italy, and Yugoslavia (Slovenia and Croatia). The authors provide an assessment of the project’s results at its midpoint, outlining its methodology and framework; its recent conference “Places of Cross-Border Interaction in History: The Alps-Adriatic Region”; and the exhibition “Never Mind the Borders. People, Places, and Cross-Border Practices between the Alps and the Adriatic”, which the research group created in both a physical and online version. The two events make a valuable contribution to the programme of the first twin European Capital of Culture, Nova Gorica/Gorizia.